2019
DOI: 10.3390/v11090767
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein YKL-40 Is Elevated and Predicts Disease Severity in Puumala Hantavirus Infection

Abstract: Most cases of hemorrhagic fever with renal syndrome (HFRS) in Europe are caused by the Puumala hantavirus (PUUV). Typical features of the disease are increased vascular permeability, acute kidney injury (AKI), and thrombocytopenia. YKL-40 is an inflammatory glycoprotein involved in various forms of acute and chronic inflammation. In the present study, we examined plasma YKL-40 levels and the associations of YKL-40 with disease severity in acute PUUV infection. A total of 79 patients treated in Tampere Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Interestingly, a study including both experimental and human data has revealed that YKL-40 may be able to discriminate been sepsis-induced acute kidney injury and sepsis without acute kidney injury [ 44 ]. In that context, patients with Puumala hantavirus infection—a virus infection typically inducing acute kidney injury—YKL-40 was more pronounced during the acute phase, and correlated with the degree of inflammation and severity of acute kidney injury [ 45 ]. These finding are in agreement with the present study demonstrating significantly higher levels plasma YKL-40 in those receiving RRT within 7 days from admission.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study including both experimental and human data has revealed that YKL-40 may be able to discriminate been sepsis-induced acute kidney injury and sepsis without acute kidney injury [ 44 ]. In that context, patients with Puumala hantavirus infection—a virus infection typically inducing acute kidney injury—YKL-40 was more pronounced during the acute phase, and correlated with the degree of inflammation and severity of acute kidney injury [ 45 ]. These finding are in agreement with the present study demonstrating significantly higher levels plasma YKL-40 in those receiving RRT within 7 days from admission.…”
Section: Discussionmentioning
confidence: 99%
“…A marker reliably predicting the severity and prognosis of HFRS would be of clinical relevance, since it could help clinicians in individualized therapy allocation based on the disease severity. In recent years, some studies have identified several early predictors related to the severity and prognosis of HFRS, such as growth arrest-specific 6 protein, urinary neutrophil gelatinase-associated lipocalin and Glycoprotein YKL-40 [ 20 22 ]. In this study, we observed that high levels of pentraxin-3 (> 569.088 ng/mL) during the acute phase were significantly associated with the death in HFRS patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In PUUV infection, plasma YKL-40 levels are elevated during the acute phase [94]. Plasma YKL-40 level associates with the length of hospital stay, which reflects the overall severity of the infection.…”
Section: Ykl-40mentioning
confidence: 99%
“…Plasma YKL-40 level associates with the length of hospital stay, which reflects the overall severity of the infection. In addition, also in terms of inflammation and AKI, YKL-40 predicts the severity of the disease caused by PUUV [94]. Furthermore, plasma YKL-40 levels remain elevated during the acute phase of PUUV infection as a sign of undergoing inflammation [94].…”
Section: Ykl-40mentioning
confidence: 99%
See 1 more Smart Citation